Model Penguatan Kevikepan Teritorial Keuskupan Surabaya 2026-2030 - Laksito, Petrus Canisius Edi; Gunawan, Theodorus Christian; Poa, Nicholaus Damianus; Kleden, Henrikus Balzano Conte; Yubileo, Yustinus (Lux et Sal, 2025)
The Diocese of Surabaya has experienced significant growth in the number of parishes; however, this expansion has also produced structural imbalances. The development of local units (parishes) has not been accompanied by a corresponding strengthening of intermediate structures (episcopal vicariates). This study addresses the issue of the "missing vicariates" (kevikepan yang hilang) marked by weak institutional functions and the limited leadership role of the Episcopal Vicar, who lacks a clear job description and strategic direction. As a result, a "silo mentality" and parochialism threaten the Church’s fundamental vision as communion. Employing a literature review as the methodological approach, this paper proposes a "Strengthening Model for Territorial Vicariates" for the period 2026–2030, aligned with the stages of the Diocese's Basic Directions (ARDAS). The framework integrates John Kotter's 8-Steps Change Model and Kurt Lewin’s 3-Phases Change Model with contemporary leadership theories: transformational, servant, authentic, and leader-member exchange (LMX). The strengthening process is structured into three phases: (1) creating a climate for change, (2) involving and empowering the entire vicariate, and (3) implementing and consolidating the culture. These phases must be accompanied by a transformation of the Episcopal Vicar’s role into that of a strategic leader and by the establishment of a solid steering coalition. In this way, vicariates can become coordinating centers that foster synodality, subsidiarity, and solidarity, ensuring the Diocese of Surabaya advances as a cohesive and missionary community.